Evidence for both visual and olfactory signalling relating to the preorbital gland in the forest-dwelling Visayan spotted deer (Rusa alfredi) - Munir, Hajra; Ward, Matt; Liprado, Ermae; Ceacero, Francisco (Journal of Vertebrate Biology, 2025)
The manuscript examines the patterns of the opening and use of the preorbital gland in the Visayan spotted deer (Rusa alfredi) and its diverse signalling role. This study focused on two captive herds of Visayan spotted deer observed across different social contexts and revealed a variety of behaviours associated with the opening of the preorbital gland, some of which have never been described previously. The findings reveal a dynamic interplay between visual and chemical signalling. As expected, preorbital gland opening for visual signalling occurred during excitement-inducing activities, such as suckling, agonistic and reproductive interactions, as well as human handling. However, it was also observed in new contexts, like during flehmen, antler rubbing, alertness towards humans, and even during relaxing activities like grooming. We also observed occurrences in young animals for the first time during low-intensity interactions like playing or mounting. The broad context of displaying this behaviour in a forest-dwelling species like the Visayan spotted deer suggests a potentially higher relevance than in species adapted to open environments. These observations contribute to our understanding of ungulate social communication.